Investigation of Microbial Community Characteristics in Pepper Rhizosphere at Seedling Stage Under Varied Soil Conditions - Yuyu ZHANG; Zhixiong CHEN; Fang CHEN; Jinqiang YAN; Junyu WU; Qingyuan XI; Shumei GE (Guangdong nongye kexue)
【Objective】The study was carried out to explore the distribution patterns of rhizospheric microbial communities in different resistant pepper varieties, aiming to provide a basis for the targeted optimization of rhizospheric microbial community structure of pepper.【Method】Taking the susceptible pepper variety 'Hailan 99' (HL99) and the resistant variety 'Sanxiaqing' (SSQ) as experimental materials, high-throughput sequencing technology was employed to analyze and compare the effects of susceptible and non-susceptible soil environments on the community diversity, species composition, correlation networks and function of bacteria and fungi in the rhizosphere soil of different disease-resistant pepper plants.【Result】Through high-throughput sequencing, a total of 66 617 operational taxonomic units (OTUs) from soil bacterial samples were obtained, among which the dominant phyla were Proteobacteria and Bacteroidetes, with the relative abundances of approximately 40.1% and 15.3%, respectively. From soil fungal samples, 2 948 OTUs were obtained, among which the dominant phylum was Ascomycota, with an average relative abundance of approximately 47.8%. The rhizospheric microbial community structure and species composition of pepper varieties showed significant differences under different soil conditions. Under susceptible soil conditions, the diversity of bacterial communities in pepper rhizosphere decreased, while the diversity of fungal communities increased. The bacterial OTUs decreased by 6.5%-7.8%, and fungal OTUs increased by 8.8%-9.8%. The relative abundance of Fusarium fungi was significantly higher in the susceptible group (5.0%) compared with that in the resistant group (4.8%), while the relative abundance of beneficial fungi like Mortierella and Trichoderma and beneficial bacteria like Pseudomonas and Bacillus was significantly lower in the susceptible group than that in the resistant group. Overall, under the susceptible soil conditions, the abundance of beneficial rhizosphere fungi and bacteria in the resistant group was higher than that in the susceptible group, contributing to a better soil micro-ecological environment. Based on species abundance tables, the correlation relationships of fungi-fungi, fungi-bacteria and bacteria-bacteria species were calculated respectively at the genus level. The results indicated that the rhizosphere microorganisms of pepper formed a complex ecological network, with high co-occurrence between fungi-fungi and fungi-bacteria (with a positive correlation percentage higher than 50%), suggesting that cooperative relationships outweighed competitive ones. The bacteria-bacteria network structure was more complex, with a positive correlation percentage of about 49.9%.【Conclusion】The rhizospheric microbial community structures of different resistant varieties exhibit significant differences under different soil conditions. The interaction of rhizosphere microorganisms forms a complex microbial ecological network structure. The relative abundance of beneficial fungi and bacteria is higher in the resistant variety than that in the susceptible variety, which suppresses more pathogenic microbes, leading to a healthier soil micro-ecological environment. The key groups identified in this study, including Fusarium, Verticillium, Trichoderma, Bacillus and Pseudomonas, will provide important information for the targeted optimization of rhizospheric microbial community structures and offer crucial theoretical references for the biological control of soil-borne diseases.